Clinical and radiographic evaluation of Curcumin Gel mixed Endoflas (CGE) powder as obturating material in primary molars - Menni, Alekhya Chowdary; Ambati, Naga Radhakrishna; Ghanashyam Prasad, Madu (Brazilian Dental Science, 2020)
Background:Zinc oxide eugenol(ZOE) has long been the material of choice for obturating primary teeth,but it is resistant to resorption, might result in a deflected successor and has limited antibacterial efficacy. Curcuminpossessesanti-inflammatory and antimicrobialproperties which can be implied by its use as obturating material in primary teeth.Objective: To evaluate and compare the efficacy of Curcumin Gel mixed Endoflas powderand Zinc oxide eugenol as obturating materials in primary molars.Material and Methods: A total of 30 primary molars indicated for pulpectomy were selected from 4-9-year-old children and divided into two equal groups based on the obturating material used. Group 1- Curcumin Gel mixed Endoflas powder(CGE) and Group 2- Zinc oxide eugenol(ZOE). The efficacy of these obturation materials was evaluatedboth clinically and radiographically. Follow-up was done after 1, 3and 6months to evaluate clinical and radiographical success rates. The results were subjected to statistical analysis using SPSS software version 21 usingchi-square test.Results: At the end of the 6th month follow-up,there was 93.3% clinical success inGroup 1compared with 86.6% success in Group 2. Whereas, radiographically success reported was 100% with Group 1and93.3% with Group 2. The difference in the radiographic success rate between the two Groups was statistically significant (P